THE IMPACT OF TRUTH OR DARE GAMES ON THE INTELLECTUAL DEVELOPMENT OF PRIMARY SCHOOL STUDENTS - Sugiarti, Iis Yeni; Apriana, Assyifa Indar (Cirebon International Conference on Education and Economics Proceeding, 2024)
This research activity was conducted to review the impact of Truth or Dare game on students' intellectual development at SD Negeri Bima Cirebon. The research method involved direct observation and the use of pre-test and post-test on grade III students. The research activities were conducted for one week (counting the preparation period). The data collected was processed in a descriptive way using statistical calculations. The results of the data showed that the Truth or Dare game was effective in increasing students' knowledge of ethical material. The average pre-test score was 82.30, while the average post-test score increased to 97.00. Most students felt happy and more excited when learning was done with this game media. The game not only improved knowledge, but also developed students' social skills and self-confidence. The researcher recommends the application of Truth or Dare game in various learning materials to reduce boredom and increase students' active participation. The learning-by-play method is proven to be effective in motivating students and making learning more interesting. Teachers are also expected to develop other game variations to maintain the diversity of learning methods and improve the overall quality of learning.